Incidence Of Campylobacter Spp. In Caecal Contents Of Broilers In Anand City, Gujarat - Tayde, R. S.; Brahmbhatt , M. N. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
A total of 60 intestinal samples (caecal content) from fresh slaughtered broiler carcass were collected from the retail meat market in and around Anand city. Forty six out of 60 (76.7 %) samples were found positive for the Campylobacter spp. The species wise high incidence rate of 82.66 % was noted for C. jejuni, whereas lower incidence rate of 10.86 % and 6.52 % was found for C. coli and other unidentified Campylobacter spp., respectively. C. jejuni was more frequently isolated indicating that this species is distributed widely in the study area.